(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Hypertension is a multifactorial and multisystem disease in which elevated blood pressure is only one sign of multiple underlying physiological abnormalities. It affects approximately 26% of the population worldwide. Hypertension is one of the leading cause of death as a "silent killer". Several classes of antihypertensive agents have been in clinical use, but CCBs exert most potent antihypertensive action and are widely used as a first line antihypertensive drug in elderly with very few contraindication.Four generations of dihydropyridines CCBs are now available.The fourth-generation highly lipophilic dihydropyridines, lercanidipine, cilnidipine and lacidipine are now available which provide a real degree of therapeutic comfort in terms of stable activity, a reduction in adverse effects and a broad therapeutic spectrum. Cilnidipine is a recently developed CCB, and possesses both L- and N-type calcium channel blocking activity.Cilnidipine causing less reflex tachycardia, less pedal edema, better control of proteinuria, suppressing podocyte damage, increasing insulin sensitivity.This article reviews the current understanding of the pharmacological profile and clinical utility of cilnidipine as a unique antihypertensive drug. Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 77-83